THE DAILY RAINFALL STATISTICAL SHIFT DURING THE HALF CENTURY OVER THE BRANTAS CATCHMENT, EAST JAVA(STATISTIK PERUBAHAN CURAH HUJAN HARIAN SELAMA SETENGAH ABAD DI DAERAH TANGKAPAN BRANTAS, JAWA TIMUR) - E. Aldrian; F Ismaini; Yonny Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2007)
A study of long term shift of the daily rainfall over the Brantas catchment East Java was done. Such a study is relatively new for the country due to lack of good quality data and sparsely distributed data all over the region. With a good quality long-term daily rainfall data over the Brantas catchment, we could detect a statistical shift of amount of rainy days, shift between periods and frequency trend changes from weekly, monthly, three-monthly and annually. The study utilized several methods including the probability density function distribution shift, Mann Kendall non parametric trend test and the wavelet analyses. The shift of low amount rainfall occurs from the dry to the wet season. We found distinct influences of orography and ENSO years in our trend tests. Additionally, the result of the Mann Kendall test show that the trend of rainy days increase during the wet season and the second transition period, while decrease during the dry season and first transitional period. Meanwhile the El Nino and La Nina have significant influence toward the dry season and the second transitional period.